CpG oligodeoxynucleotides inhibit the proliferation and osteoclastic differentiation of RAW264.7 cells. Issue 25 (15th April 2020) - Zheng, Yi; Yu, Wenwen; Li, Hongyan; Lin, Hongbing; Chen, Zhen; Chen, Huishan; Zhang, Peipei; Tian, Yue; Xu, Xiaowei; Shen, Yuqin
Abstract : Clinical prevention and treatment of periodontitis-induced bone absorption remains a challenge. Abstract : Clinical prevention and treatment of periodontitis-induced bone absorption remains a challenge. The anti-infection role of CpG oligodeoxynucleotides (CpG ODNs) is well known; however, their effect on osteoclasts is still unclear. Here, we show that some CpG ODNs can regulate osteoclastogenesis of RAW264.7 cells. The phosphorothioate CpG ODN was efficiently taken up by the cells within 1 h and distributed in the cytoplasm. BW006, YW001, YW002, and FC004 CpG ODNs significantly repressed cell proliferation by targeting several cyclin proteins to arrest the cells in the G2 phase and to further initiate cell apoptosis. Regarding differentiation, we selected six CpG ODNs (FC002, BW006, YW002, YW001, FC004, and MT01) that markedly inhibited the gene expression levels of Nfatc, c-fos, RANK, and MMP9 . TRAP staining showed that only YW002, YW001, and FC004 suppressed osteoclast generation and maturation. These three CpG ODNs dramatically declined the protein levels of osteoclastogenic proteins by elevating the ratio of OPG/RANKL and also downregulating the inflammatory factors (TNF-α, IL-1β, IL-6, and IL-17) at different stages. Thus, the selected CpG ODNs may be a potential molecular therapy for the prevention and treatment of periodontitis-mediated bone resorption.